Bartonella spp. in Small Mammals, Benin - Martin-Alonso, Aaron; Houemenou, Gualbert; Abreu-Yanes, Estefanıa; Valladares, Basilio; Feliu, Carlos; Foronda, Pilar (My University, 2016)
This study aimed to investigate the prevalence and genetic diversity of Bartonella organisms in small mammals in Cotonou, Benin. We captured 163 rodents and 12 insectivores and successfully detected Bartonella DNA from 13 of the 175 small mammal individuals. Bartonella spp., identical or closely related to Bartonella elizabethae, Bartonella tribocorum, and Bartonella rochalimae, was detected. A potential new Bartonella species, proposed as Candidatus Bartonella mastomydis, was found in three Mastomys individuals and genetically characterized by targeting two housekeeping genes (rpoB and gltA) and the intergenic species region. However, 20.8% of gray rats were found to be infected with Bartonella spp., and none of the black rats analyzed was positive. This work may be important from a public health point of view due to the zoonotic nature of the Bartonella species detected and warrants further investigation on the unknown zoonotic potential of this newly proposed Bartonella species.
Keywords: Bartonella—PCR—Rodents—Vector-borne.